The trajectory of functional status among older adults with chronic diseases and the association with social relationships - Jiao, Dandan; Zhu, Yantong; Zhu, Zhu; Li, Xiang; Zhang, Jinrui; Cui, Mingyu; Liu, Yang; Matsumoto, Munenori; Sawada, Yuko; Miura, Kumi Watanabe; Watanabe, Taeko; Anme, Tokie (Frontiers in Public Health, 2025)
BackgroundFunctional status crucially affects healthy aging. Identifying trajectory of functional status and related determinants is important. We aimed to identify the trajectory of functional status over 6 years among older adults with chronic diseases and its association with social relationships.MethodsA latent class growth model analysis was conducted to explore the trajectory of functional status using three time points over 6 years. After identifying the trajectories, a multi-nominal logistic regression analysis was performed to examine the association between social relationships and the trajectories.ResultsWe included data from 458 participants aged ≥65 years with chronic diseases in Japan. Three distinct trajectories were identified, with 73.3% of participants being functionally stable, 16.6% moderate functional decline, and 10.1% rapid functional decline. Good social relationships were associated with a lower probability of having moderate or rapid functional decline trajectories (odds ratio [OR] 0.75, 95% confidence interval [CI] 0.65–0.87 and OR 0.63, 95% CI 0.51–0.78, respectively).ConclusionDifferences were found in the functional trajectories of older adults with chronic disease over time. Older adults with more extensive social relationships appeared less likely to have a poorer functional trajectory. The findings suggest that fostering extensive social relationships could be an effective management strategy for functional decline deterioration.